Neurological outcomes and mortality of hyperoxaemia in patients with acute brain injury: protocol for a systematic review and meta-analysis - Chiara Robba; Rafael Badenes; Fabio Silvio Taccone; Nekane Romero-Garcia; Berta Monleon; Ana Ruiz-Zarco; Alberto Ruiz-Pacheco; Maria Pascual-Gonzalez; Felipe Perdomo; Maria Luisa Garcia-Perez (BMJ Open)
Introduction Oxygen is frequently prescribed in neurocritical care units. Avoiding hypoxaemia is a key objective in patients with acute brain injury (ABI). However, several studies suggest that hyperoxaemia may also be related to higher mortality and poor neurological outcomes in these patients. The evidence in this direction is still controversial due to the limited number of prospective studies, the lack of a common definition for hyperoxaemia, the heterogeneity in experimental designs and the different causes of ABI. To explore the correlation between hyperoxaemia and poor neurological outcomes and mortality in hospitalised adult patients with ABI, we will conduct a systematic review and meta-analysis of observational studies and RCTs.Methods and analysis The systematic review methods have been defined according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and follow the PRISMA-Protocols structure. Studies published until June 2024 will be identified in the electronic databases MEDLINE, Embase, Scopus, Web of Science, The Cochrane Library, Cumulative Index to Nursing and Allied Health Literature and ClinicalTrials.gov. Retrieved records will be independently screened by four authors working in pairs, and the selected variables will be extracted from studies reporting data on the effect of ‘hyperoxaemia’ versus ‘no hyperoxaemia on neurological outcomes and mortality in hospitalised patients with ABI. We will use covariate-adjusted ORs as outcome measures when reported since they account for potential cofounders and provide a more accurate estimate of the association between hyperoxaemia and outcomes; when not available, we will use univariate ORs. If the study presents the results as relative risks, it will be considered equivalent to the OR as long as the prevalence of the condition is close to 10%. Pooled estimates of both outcomes will be calculated applying random-effects meta-analysis. Interstudy heterogeneity will be assessed using the I2 statistic; risk of bias will be assessed through Risk Of Bias In Non-Randomised Studies of Interventions, Newcastle-Ottawa or RoB2 tools. Depending on data availability, we plan to conduct subgroup analyses by ABI type (traumatic brain injury, postcardiac arrest, subarachnoid haemorrhage, intracerebral haemorrhage and ischaemic stroke), arterial partial pressure of oxygen values, study quality, study time, neurological scores and other selected clinical variables of interest.Ethics and dissemination Specific ethics approval consent is not required as this is a review of previously published anonymised data. Results of the study will be shared with the scientific community via publication in a peer-reviewed journal and presentation at relevant conferences and workshops. It will also be shared key stakeholders, such as national or international health authorities, healthcare professionals and the general population, via scientific outreach journals and research institutes’ newsletters.